History of studying essential oil crops - Zh. A. Shaova; V. N. Kosarev; M. S. Galicheva (Вестник Майкопского государственного технологического университета, 2024)
The article provides a historical overview of the formation and development of the essential oil industry. The main attention is paid to the history of scientific research of essential oil and medicinal plants. Our ancestors may have instinctively selected certain herbs for healing, just as sick animals today seek out plants they wouldn't normally eat. Based on an analysis of the current state, the need has been determined and the priority tasks have been formed for a full-scale revival of essential oil production in the Russian Federation.The problem tatement: in the republics of the former USSR, a number of essential oil plants were cultivated: coriander, lavender, essential oil rose, sage and others. In the 1970-80s the area of cultivation of essential oil plants exceeded 200 thousand hectares. At the same time, the demand for essential oils and other essential oil products was not fully satisfied. With the collapse of the USSR, the essential oil industry declined. The growing areas for most of the essential oil crops ended up on the territory of the newly formed independent states. The cultivation and processing of essential oils in Russia decreased significantly.The goal of the research is substantiation and acquisition of knowledge about the history of emergence and development of essential oil plants, herbal medicine, active substances as a tool for developing a common problem and combining the scientific, industrial and innovative potential of all interested parties.The research methods used are source study, historical-typological and biographical methods. The research results: the opportunity to gain new knowledge about the history of the origin and distribution of essential oil plants, and the creation of a huge food base for animals and people.